Perceived helpfulness of bipolar disorder treatment: Findings from the World Health Organization World Mental Health Surveys. (28th March 2021) - Nierenberg, Andrew A.; Harris, Meredith G.; Kazdin, Alan E.; Puac‐Polanco, Victor; Sampson, Nancy; Vigo, Daniel V.; Chiu, Wai Tat; Ziobrowski, Hannah N.; Alonso, Jordi; Altwaijri, Yasmin; Borges, Guilherme; Bunting, Brendan; et al.
Abstract: Objectives: To examine patterns and predictors of perceived treatment helpfulness for mania/hypomania and associated depression in the WHO World Mental Health Surveys. Methods: Face‐to‐face interviews with community samples across 15 countries found n = 2, 178 who received lifetime mania/hypomania treatment and n = 624 with lifetime mania/hypomania who received lifetime major depression treatment. These respondents were asked whether treatment was ever helpful and, if so, the number of professionals seen before receiving helpful treatment. Patterns and predictors of treatment helpfulness were examined separately for mania/hypomania and depression. Results: 63.1% (mania/hypomania) and 65.1% (depression) of patients reported ever receiving helpful treatment. However, only 24.5–22.5% were helped by the first professional seen, which means that the others needed to persist in help seeking after initial unhelpful treatments in order to find helpful treatment. Projections find only 22.9% (mania/hypomania) and 43.3% (depression) would persist through a series of unhelpful treatments but that the proportion helped would increase substantially if persistence increased. Few patient‐level significant predictors of helpful treatment emerged and none consistently either across the two components (i.e., provider‐level helpfulness and persistence after earlier unhelpful treatment) or for both mania/hypomania and depression. Although prevalence of treatment was higher in high‐income than low/middle‐income countries, proportional helpfulness among treated cases was nearly identical in the two groups of countries. Conclusions: Probability of patients with mania/hypomania and associated depression obtaining helpful treatment might increase substantially if persistence in help‐seeking increased after initially unhelpful treatments, although this could require seeing numerous additional treatment providers. In addition to investigating reasons for initial treatments not being helpful, messages reinforcing the importance of persistence should be emphasized to patients.